Experimental demonstration of bi-directional laser ranging and data communication for space gravitational wave detection - Peiquan Chen; Yibin Zhang; Rujie Deng; Heshan Liu; Ziren Luo (Results in Physics)
In this study, we designed ranging parameters and refined a loop filtering algorithm to solve the problem of parameter compatibility with the phasemeter and low ranging accuracy under bidirectional communication conditions. This enables the ranging and communication system to be integrated directly into the phasemeter as an auxiliary module. Experimental results compare fiber measurement lengths under different clock sources, indicating that the system achieves an ranging accuracy of 82.1 cm with an rms error of 9.14 cm. Additionally, the data communication rate reaches 19.5 kbps with a bit error rate below 10−6, all while ensuring that the implementation of the laser ranging and data communication system utilizes only 1% of the optical power to avoid introducing excessive phase noise to the scientific interferometer.